Regulation on the Utilization of Carbon Service as a Forest Protection Effort in Indonesia - Abdhy Walid Siagian; Syofiarti; Anton Rosari (The Journal of Indonesia Sustainable Development Planning, 2023)
Reducing Emissions from Deforestation and Forest Degradation (REDD+) is a strategy to reduce greenhouse gas emissions from deforestation and forest degradation. Through this scheme, Indonesia is vital in implementing ratified commitments through national legislation. The methodology used in the research employed normative juridical techniques characterized by descriptive research parameters and underwent analysis through comprehensive literature exploration. The results found that Indonesia has supported sustainable development by issuing REDD+ arrangements to realize climate change mitigation. Through the REDD+ scheme, Indonesia is expected to provide answers to global warming problems that occur throughout the world by providing protection, preventing degradation, and providing an increase in the quality of forest cover and carbon stocks.